Treatment of Amalgam Tattoo With a New Technique: Mucoabrasion and Free Connective Tissue Graft. Issue 3 (15th April 2019) - Aguirre‐Zorzano, Luis Antonio; García‐De‐La‐Fuente, Ana M.; Estefanía‐Fresco, Ruth
Abstract : Introduction: A new technique was performed for the removal of an amalgam tattoo (AT), consisting in mucoabrasion combined with a free connective tissue graft (FCTG). Case Presentation: A 59‐year‐old female presented with a large AT involving the alveolar mucosa and gingiva between teeth #7 and #8, where endodontic treatment and apicoectomy was performed 21 years ago. To avoid compromising esthetics, the lesion was managed with a new technique including mucoabrasion and an FCTG. At the 53‐month follow‐up, the patient exhibited a naturally appearing soft tissue with no evidence of the AT. Conclusion: When performing a one‐stage treatment of removing ATs in areas of high esthetic demand, it is possible to achieve good results and ideal gingival color.